Kinerja Karyawan pada Perseroan Terbatas MGS Berkarya Mandiri di Kabupaten Sigi - Tinungki, Reza Angga Saputra; Halim, Rahmawati; Munari, Munari (AURELIA: Jurnal Penelitian dan Pengabdian Masyarakat Indonesia, 2026)
The results of this study indicate that Employee Performance at PT. MGS Berkarya Mandiri, Sigi Regency has not been running optimally, this is caused by the failure to achieve the performance indicators used in this study, such as the quality aspect which has not been optimal due to the low responsiveness, discipline, and accuracy of the employees in the company in carrying out their duties. The quantity aspect has not been optimal because there are still a number of activities that do not reach the target. The punctuality aspect has not been running optimally due to frequent delays in completing tasks. The effectiveness aspect has been running optimally due to the large number of facility and infrastructure resources allocated to support each employee's activities in the company to achieve the desired results in several work units. The independence aspect has not been running optimally because there are still some employees who actually transfer their tasks and work to other employees where the work should be completed by employees in their fields. The interpersonal impact aspect has been running optimally because the work commitment of employees in the company is quite good towards what is their obligation as employees